A revised terrace stratigraphy and chronology for the early Middle Pleistocene Bytham River in the Breckland of East Anglia, UK. (1st October 2021) - Lewis, Simon G.; Ashton, Nick; Davis, Rob; Hatch, Marcus; Hoare, Peter G.; Voinchet, Pierre; Bahain, Jean-Jacques
Abstract: The Bytham River was one of the major pre-Anglian (MIS 12) rivers of eastern England. Flowing from the Midlands to the East Anglian coast, it has been recognised at numerous sites by its distinctive lithological suite, containing significant quantities of quartzite, quartz and Carboniferous chert that originate from central England. In the Breckland of Suffolk and Norfolk, deposits of the Bytham River can be identified at 26 sites by this distinctive clast lithological composition. These sediments, referred to as the Ingham Formation, consist of a series of sand and gravel aggradations, which due to their differences in elevation can be interpreted as at least four early Middle Pleistocene terrace remnants of the former river, and a final phase of deposition along the river valley prior to its destruction. This paper reports on recent fieldwork at six of these sites, which through stratigraphic and lithological analyses, together with new Electron Spin Resonance age estimates, contribute to a revised geological framework for the Bytham River as represented in the Breckland. These sites can be attributed to the four lowest fluvial aggradations, with the lowest and youngest of these aggradations shown to be early Anglian in age. The river was subsequently overrun by Anglian ice during Marine Isotope Stage 12. This revised geological and chronological interpretation provides an important framework for understanding the Lower Palaeolithic artefacts that have been found within these gravel aggradations, and contributes to the understanding of the human occupation of north-west Europe during the early Middle Pleistocene. Highlights: Report on field investigations at six sites attributed to the Bytham River, UK. Six aggradations with height differences representing terrace remnants, identified. Lithostratigraphy and ESR ages place the deposits in the early Middle Pleistocene. Terraces provide framework for dating the contained Lower Palaeolithic archaeology. Bytham archaeology furthers understanding of the early human occupation of Europe.